Quantitative breast tissue characterization using grating-based x-ray phase-contrast imaging - Willner, M.; Herzen, Julia; Grandl, S.; Auweter, S.; Mayr, D.; Hipp, A.; Chabior, M.; Sarapata, A.; Achterhold, Klaus; Zanette, I.; Weitkamp, Timm; Sztrokay, A.; et al. (Physics in Medicine and Biology, 2014)
X-ray phase-contrast imaging has received growing interest in recent years due to its high capability in visualizing soft tissue. Breast imaging became the focus of particular attention as it is considered the most promising candidate for a first clinical application of this contrast modality. In this study, we investigate quantitative breast tissue characterization using grating-based phase-contrast computed tomography (CT) at conventional polychromatic x-ray sources. Different breast specimens have been scanned at a laboratory phase-contrast imaging setup and were correlated to histopathology. Ascertained tumor types include phylloides tumor, fibroadenoma and infiltrating lobular carcinoma. Identified tissue types comprising adipose, fibroglandular and tumor tissue have been analyzed in terms of phase-contrast Hounsfield units and are compared to high-quality, high-resolution data obtained with monochromatic synchrotron radiation, as well as calculated values based on tabulated tissue properties. The results give a good impression of the method's prospects and limitations for potential tumor detection and the associated demands on such a phase-contrast breast CT system. Furthermore, the evaluated quantitative tissue values serve as a reference for simulations and the design of dedicated phantoms for phase-contrast mammography. © 2014 Institute of Physics and Engineering in Medicine.
CRIS-Team Scopus Importer:2023-03-08
Keywords: breast imaging; computed tomography; phase contrast; tissue properties; x-ray imaging